Ngrowot Tradition in Neuroscience Study in Luqmaniyah Islamic Boarding School, Yogyakarta - Suyadi Suyadi; Mawi Khusni Albar (IBDA` : Jurnal Kajian Islam dan Budaya, 2018)
The purpose of this research is to discuss a sacred and a transcendence tradition of ngrowot at PPLQ in the perspective of a medic and a scientific neuroscience. All of data that was correlated with the ngrowot tradition was categorized empirically and scientifically, and then it was analyzed through neuroplasticity theory explaining the brain that can be transformed by behavioral changes. The result of this study explained that the philosophy of ngrowot is theology and food sovereignty. In the modern era, ngrowot becomes a healthy lifestyle for some elite that is called as the â€œhealthy dietâ€. This research develops food theology in terms of Islamic educational neuroscience into theology of intelligence and the sovereignty of thinking. The theology of intelligence makes ngrowot as tirakat during the learning process in order to get barokah in terms of the intelligence aspects, and get the benefits in the world and the hereafter. The sovereignty of thinking makes ngrowot as laku prihatin so a salafistâ€™s intelligence of ngrowot cannot be easily interrupted by the secular idea that is not appropriate with Islamic spiritual teachings. The behavioral changes of ngrowot believers also implicate to the structure of neuron in the mind. So, ngrowot can be an educational character method, and in the same time, it also develops the intelligence of ngrowot believera in any dimensions.